The Phenomenon of the Hijrah Trend in the Millennial Era and Its Relevance to Hadith - Putri Azka Syofarina; Muhajirin; Hedhri Nadhiran (Al-Bukhari : Jurnal Ilmu Hadis, 2025)
This study aims to analyze the phenomenon of the hijrah trend among the millennial generation and its relevance to the teachings of Hadith. Originally understood as a physical and spiritual migration, the hijrah phenomenon has rapidly developed among millennials as a form of searching for meaning in life and self-identity. Through a qualitative approach and literature study, this research examines the driving factors behind the hijrah trend, including the influence of social media, popular culture, and spiritual awareness. Additionally, the study explores the relevance of the hijrah practices undertaken by millennials in relation to Hadiths that discuss self-transformation and the upholding of Islamic values. The results indicate that the hijrah trend among millennials is not merely a social phenomenon but also a manifestation of their efforts to affirm Islamic identity and seek inner peace, in accordance with Hadith teachings. This research is expected to provide a deeper understanding of the socio-religious dynamics in the millennial era and its contribution to strengthening Islamic identity in modern society.